Pharmacokinetics of aztreonam in patients with various degrees of renal dysfunction. - Mihindu, J C (1983)
We have studied the pharmacokinetics of 1-g intravenous doses of aztreonam in four groups of six volunteers each, distinguished by their creatinine clearances (greater than 80, 30 to 80, 10 to 29, and less than 10 ml/min). Subjects received 1 g of aztreonam intravenously without any complications. Aztreonam serum and urine levels were measured by microbiological methods and by high-pressure liquid chromatography, and unbound serum aztreonam was determined by ultrafiltration. Serum levels were well described by a two-compartment infusion model. From this model we determined steady-state volume of distribution, alpha distribution phase half-life, beta elimination phase half-life, and total clearance of aztreonam. The mean of beta elimination phase half-life ranged from 2 h in normal subjects to 6 h in anephric patients. The total clearance of aztreonam correlated closely with corrected creatinine clearance calculated from serum creatinine, age, and sex (r = 0.97, P less than 0.001) and ranged from a mean value of 107 ml/min in normal subjects to 29 ml/min in functionally anephric patients. Some 75% of aztreonam excretion was renal. Urinary recovery of aztreonam ranged from 58% of the administered dose in normal subjects to 1.4% in uremic patients. Free aztreonam in serum correlated inversely with creatinine clearance (P less than 0.001). A nomogram was developed as a guide for adjustment of aztreonam dosage according to renal function.